Validity And Reliability of he English Summative Test For Second Semester of he Fifth Grade in Academic Year 2019/2020 - Nisa, Khairunnisa; Pulungan, Anni Holila; Husein, Rahmad (International Journal of Educational Research & Social Sciences, 2021)
The validity and reliability of the test is very important before the test is used to measure student achievement. This study aims to analyze the validity and reliability of the summative English test for fifth grade public elementary schools 058238 Bukit Rata in the academic year 2019/2020, and to investigate the quality level of the summative test of English in elementary schools. This research is a quantitative descriptive study. The subjects in this study were students of grade V public elementary school 058238 Bukit Rata in the academic year 2019/2020. The data analysis technique used is quantitative analysis by testing the validity, reliability, level of difficulty, distinguishing power, and tricking effectiveness. The data obtained were analyzed using the ANATES version 4 program and manual calculations using Microsoft Excel. The results showed that, the level of validity of the English test in grade 5 elementary school before the revision based on material aspects, construct aspects and language aspects obtained a percentage of 73% with a good category. After being revised, based on material aspects, construct aspects and language aspects obtained a percentage of 90% with a good category. The reliability test was carried out twice, namely the questions before expert validation and after expert validation. The results of the reliability test on the first question were the value of -0.084 in the unreliable category because the value was ≤ 0.700. Furthermore, the second test of English test reliability was carried out. The results of the second test reliability test, namely the KR 20 formula with the help of the Excel program obtained a value of 0.413 in the sufficient category. The level of validity and reliability of the English test in grade 5 elementary schools. Before the revision, the number of valid questions was 4 valid questions or 16% of the total questions. Furthermore, the number of questions that can be accepted is 17 questions, but 13 questions are not valid. So it is necessary to improve the overall problem. After the revision was made, the number of valid questions was 16 valid questions or 64% of the total questions. Furthermore, the number of questions that can be used is 15 questions, because one significant question has a low difference power, so the question is not used. The validity and reliability of the English test in fifth grade public elementary school 058238 Bukit Rata should be revised becausereliability is used as an indicator in believing the value of a test because it has consistency. While the test must be valid because it is used as a development and evaluation of a test. In addition, validity is also needed to determine the feasibility of items.